CRISPR/Cas9-mediated miR-21 editing in high-grade urothelial carcinoma cells and its biological effects - Maria Carolina Yi Lin Lee; Juliana Alves Camargo; Giovana Caetano Vilas Boas; Karina Serafim Silva; Luana Pereira Silva; Carolina Mie Mioshi; Ruan Pimenta; Iran Amorim Silva; Katia Ramos Moreira Leite; William Carlos Nahas; Sabrina T dos Reis (Molecular Biology Reports, 2026)
Background Urothelial carcinoma, the predominant form of bladder cancer, represents a global public health challenge due to its high rates of recurrence and progression. At the molecular level, microRNA-21 (miR-21) has been characterized as an “oncomir” because of its ability to negatively regulate tumor suppressor genes, thereby promoting tumor survival and progression. In this context, the CRISPR/Cas9 system has emerged as a precise genome-editing tool. Objective To investigate the biological effects of miR-21 modulation using CRISPR/Cas9-mediated genome editing in the T24 high-grade invasive urothelial carcinoma cell line. Methods The CRISPR/Cas9 system was delivered as a ribonucleoprotein (RNP) complex. Editing efficiency was assessed using quantitative reverse transcription PCR (RT-qPCR). Functional effects were evaluated through gene expression assays, cell migration assays, as well as Matrigel invasion assays. The presence of the Cas9 protein was confirmed by immunofluorescence. Results CRISPR/Cas9 treatment targeting miR-21 showed a trend toward reduced miR-21 expression (p = 0.0563), although this did not reach statistical significance. A statistically significant increase in MASPIN (p < 0.0001) and PDCD4 (p = 0.0239), as well as a trend toward increased PTEN expression (p = 0.055), was observed following treatment. Functionally, a significant reduction in the migratory capacity of edited cells was observed after 48 h (p = 0.0334). The presence of Cas9 was successfully confirmed in transfected cells. Conclusion These findings suggest that CRISPR/Cas9-mediated modulation of miR-21 may influence tumor suppressor pathways and reduce the migratory potential of urothelial carcinoma cells.